Hormonal drugs for veterinary usein the pharmaceutical market: assortment analysis - Evgeny A. Belousov; Ekaterina O. Novikova; Mikhail M. Karasev; Olga V. Belousova; Elena A. Notina; Oleg O. Novikov (RUDN Journal of Agronomy and Animal Industries)
Medicines are successfully used to correct physiological and biochemical processes, primarily to intensify the development of the animal organism in agriculture. Registered medicinal products for veterinary use comprises 2384 units. Modern pharmacology has a wide range of drugs that contribute to faster development to increase the muscle mass of the animal and significantly reduce costs for obtaining marketable products. Hence the attention paid to hormonal drugs by zootechnical and veterinary services. The results of a marketing study of the veterinary use drugs range that are offi registered in the specialized market of the Russian Federation are presented. The study was conducted to ensure the target consumer market. The results obtained will increase the awareness of specialized specialists, expand their professional horizons and, as a result, improve the coordination of material, labor and financial assets of the veterinary organization and its activities in general.